Effects of crocin and safranal, saffron constituents, on the formalin-induced orofacial pain in rats - Erfanparast, Amir (Avicenna J Phytomed, 2015)
OBJECTIVE: Crocin and safranal are the main components of saffron, and have many biological functions such as anti-inflammatory and antioxidant activities. In the present study, we investigated the effects of crocin, safranal, morphine, diclofenac and naloxone in combined and separately on formalin-induced orofacial pain in rats. MATERIALS AND METHODS: Subcutaneous injection of a diluted formalin solution (50 µl, 1.5%) into the upper lip region produced a biphasic pattern of pain response (a neurogenic phase: 0-3 min and an inflammatory phase: 15-33 min). The time each animal spent face rubbing with ipsilateral forepaw was recorded and considered as an index of nociception RESULTS: Intraperitoneal injections of crocin (12.5 and 25 mg/kg), safranal (0.25 and 0.5 mg/kg), diclofenac (5 and 10 mg/kg) and morphine (1 and 2 mg/kg) suppressed the second phase of pain. The second phase of pain was also reduced when low (ineffective) doses of crocin (6.25 mg/kg) and safranal (0.125 mg/kg) were co-administered with low doses of diclofenac (2.5 mg/kg) and morphine (0.5 mg/kg). The more antinociceptive effects were observed when the medium doses of the above-mentioned chemicals used together. Naloxone prevented morphine-induced antinociception, but did not inhibit the suppressive effects of crocin and safranal. Safranal at a high dose (0.5 mg/kg) suppressed locomotor activity. CONCLUSION: The present results showed antinociceptive effects for crocin and safranal in inflammatory pain. Opioid receptors may not be involved in the antinociceptive effect of crocin and safranal. Crocin and safranal increased diclofenac-induced antinociception.